Pengembangan Kurikulum Merdeka Terhadap Pembelajaran Pendidikan Agama Islam (PAI) di Madrasah - Eka Mayasari Eka Mayasari (STAI Nusantara Banda Aceh, 2005)
This research aims to analyze the development of the independent curriculum and methodology for Islamic Religious Education in schools in relation to the regulations that establish the Independent Curriculum as the basic framework and curriculum structure for all educational units in Indonesia. With a qualitative approach, data is collected through document analysis. This writing method uses a literature review to manage data with descriptive analysis presented systematically and objectively. From the research results, there are five principles that are applied to the development of the PAI curriculum. These principles include theological principles, philosophical principles, psychological principles, socio-cultural principles, scientific and technological principles. The application of these five principles includes theological principles using the Al-Qur'an and Hadith, philosophical principles using a combination of concepts from philosophical schools, psychological principles determining abilities according to level, socio-cultural principles emphasizing the introduction of culture, and science and technology principles maximizing technological development towards Learning Activities. The conclusion of this research is that the implementation of the principles of curriculum development contributes to the development of the Islamic religious education curriculum theoretically and practically for both educators, students, school institutions and the community and can be a complement to the authorities in formulating decisions regarding the Islamic religious education curriculum.